Kinetic Study of the Hydrogen Oxidation Reaction on Nanostructured Iridium Electrodes in Acid Solutions - Montero, María de Los Angeles (2013)
The hydrogen oxidation reaction was studied on a rotating disc electrode of nanostructured iridium supported on glassy carbon. The electrode was prepared via sputtering and further annealing at 400ºC under hydrogen atmosphere in order to avoid the presence of iridium oxide. The iridium film was analyzed by microscopic (SEM, AFM), spectroscopic (XRD and XPS) and electrochemical (cyclic voltammetry) techniques, which allowed to verify the nanostructured morphology and the absence of any phase other than metallic iridium. The real surface area was evaluated by adsorption of UPD hydrogen and CO stripping. Experimental current ? overpotential (E) curves of the hydrogen oxidation reaction were obtained in the range comprised between -0.03 V and 0.20 V at different rotation rates in sulphuric acid solution. They were correlated by kinetic expressions and the corresponding values of the kinetic parameters were evaluated. It was verified that over this overpotential region the reaction proceeds almost purely through the Tafel-Volmer route. Moreover, an exchange current density jo = 1.34 mA cm-2 was calculated.